Functional Intricacy and Symmetry of Long Non-Coding RNAs in Parasitic Infections - Olajide, Joshua Seun; Olopade, Bolatito; Cai, Jianping (Frontiers in Cellular and Infection Microbiology, 2021)
RNAs are a class of molecules and the majority in eukaryotes are arbitrarily termed non- coding transcripts which are broadly classified as short and long non-coding RNAs. Recently, knowledge of the identification and functions of long non-coding RNAs have continued to accumulate and they are being recognized as important molecules that regulate parasite-host interface, parasite differentiation, host responses, and disease progression. Herein, we present and integrate the functions of host and parasite long non-coding RNAs during infections within the context of epigenetic re-programming and molecular crosstalk in the course of host-parasite interactions. Also, the modular range of parasite and host long non-coding RNAs in coordinated parasite developmental changes and host immune dynamic landscapes are discussed. We equally canvass the prospects of long non-coding RNAs in disease diagnosis and prognosis. Hindsight and suggestions are offered with the aim that it will bolster our understanding for future works on host and parasite long non-coding RNAs.